Electron-Beam-Pumped UVC Emitters Based on an (Al,Ga)N Material System - Valentin Jmerik; Vladimir Kozlovsky; Xinqiang Wang (Nanomaterials, 2023)
Powerful emitters of ultraviolet C (UVC) light in the wavelength range of 230–280 nm are necessary for the development of effective and safe optical disinfection technologies, highly sensitive optical spectroscopy and non-line-of-sight optical communication. This review considers UVC emitters with electron-beam pumping of heterostructures with quantum wells in an (Al,Ga)N material system. The important advantages of these emitters are the absence of the critical problem of p-type doping and the possibility of achieving record (up to several tens of watts for peak values) output optical power values in the UVC range. The review consistently considers about a decade of world experience in the implementation of various UV emitters with various types of thermionic, field-emission, and plasma-cathode electron guns (sources) used to excite various designs of active (light-emitting) regions in heterostructures with quantum wells of AlxGa1−xN/AlyGa1−yN (x = 0–0.5, y = 0.6–1), fabricated either by metal-organic chemical vapor deposition or by plasma-activated molecular beam epitaxy. Special attention is paid to the production of heterostructures with multiple quantum wells/two-dimensional (2D) quantum disks of GaN/AlN with a monolayer’s (1 ML~0.25 nm) thickness, which ensures a high internal quantum efficiency of radiative recombination in the UVC range, low elastic stresses in heterostructures, and high-output UVC-optical powers.